Availability Equivalence Analysis of a Repairable Series-Parallel System. (21st February 2012) - Hu, Linmin; Yue, Dequan; Zhao, Dongmei
Abstract : This paper studies the availability equivalence of different designs of a repairable series-parallel system. Under the assumption that the system components have constant failure rates and repair rates, we derive the availability of the original and improved systems according to reduction, increase, hot duplication, warm duplication and cold duplication methods, respectively. The availability equivalence factor is introduced to compare different system designs. Two types of availability equivalence factors of the system are obtained. Numerical examples are provided to interpret how to utilize the obtained results.